Summer Distribution of Bowhead Whales, Balaena mysticetus, Relative to Oil Industry Activities in the Canadian Beaufort Sea, 1980-84 - Richardson, W. John; Davis, Rolph A.; Evans, C. Robert; Ljungblad, Donald K.; Norton, Pamela (ARCTIC, 1987)
Aerial surveys in 1980-84 showed that summer distribution of bowheads in the Beaufort Sea varied markedly between years. Distribution varied both outside and within the "main industrial area" (MIA), the area of island construction, drilling and intensive ship and helicopter traffic. Numbers of bowheads in the MIA were high in 1980, lower in 1981, near zero in 1982 and very low in 1983-84. The few whales in the MIA in 1983-84 were mainly near its edges, contrary to 1980-81. These data, plus limited evidence from 1976-79, indicate that bowheads were numerous in the centre of the MIA in 3 of 5 years from 1976-80 (1976-77, 1980) vs. 0 of 4 years from 1981-84. One hypothesis is that progressively increasing industrial activities affected bowhead distribution after 1980. However, bowheads probably also react to variations in their zooplankton prey, which may be affected by year-to-year changes in oceanography and weather. Influences of natural factors on zooplankton and bowheads need to be better understood in order to assess whether oil exploration caused any of the observed changes in bowhead distribution.Key words: bowhead whale, Balaena mysticetus, Beaufort Sea, oil exploration, seismic exploration, aerial surveys Des relevés aériens effectués entre 1980 et 1984 ont montré que la répartition estivale des baleines franches dans la mer de Beaufort varie nettement d’année en année. Elle varie à fois à l’extérieure et à l’intérieur de la “zone industrielle principale” (ZIP), qui est la zone de construction de l’île, de forage et de circulation intense de bateaux et d’hélicoptères. Le nombre de baleines franches dans la ZIP était élevé en 1980, plus bas en 1981, près de zéro en 1982, et très bas en 1983 et 1984. Les quelques baleines présentes dans la ZIP en 1983 et 1984 étaient principalement à la périphérie, contrairement à 1980 et 1981. Ces données, jointes à des évidences plus limitées de 1976 à 1979, indiquent que les baleines franches étaient nombreuses au centre de la ZIP pendant 3 années sur 5, allant de 1976 ...